A Performance Analysis of Village Fund Management: A Case Study in Lut Tawar District – Indonesia - Bustaman Bustaman; Erlisa Amalia; Jalaluddin Jalaluddin (Journal of Accounting Research, Organization and Economics, 2018)
AbstractObjective – This study aims to analyze the performance of village governments in managing financial resources of the budget year 2016 in Lut Tawar District, Central Aceh Regency, according to the Indonesian Minister of Home Affairs Regulation (or PERMENDAGRI) No. 113, 2014. Design/methodology – This research is a descriptive research with a qualitative approach is a type of research where the researcher describes or deeply analyzes the result of a research about an object and then adds it with sources which already existed in the research object. The data was gathered through number of interviews and document analysis.  Results – The result of the research shows that the performance of the village government in managing fund allocation in Lut Tawar Sub-district at the planning stage has been running well. The implementation stage has been completed where all the programs and activities are executed in accordance with the plan. The administrative stage has been done well by the treasurers and every month the treasurers have accounted for every acceptance and expenditure to the village headmen. In the reporting stage, the delay in submitting accountability report is caused by some negligence by the party from the village government. At the accountability stage, the accountability reports were reported as well as evaluated with the village government community and transparent to the community for every use of village funds in the form of information posted on the information boards in the office of the village headmen and billboards installed in front of the village headman office.